Health Inequality Monitoring channel on OpenWHO: capacity strengthening through eLearning - Nicole Bergen; Katherine Kirkby; Andreia Baptista; Devaki Nambiar; Anne Schlotheuber; Cecilia Vidal Fuertes; Ahmad Reza Hosseinpoor (BMC, 2022)
Abstract Background Health inequality monitoring can generate important evidence to inform and motivate changes to policy, programmes and practices. However, the potential of health inequality monitoring practices to quantify inequalities between population subgroups and track progress on the advancement of health equity is under-realized. Capacity strengthening on health inequality monitoring can play an important role in enhancing political will for the generation and use of disaggregated data and for wider adoption of this practice to inform health decision-making. There is a lack of widely available and accessible training materials related to health inequality monitoring that may be used by a range of stakeholders. Objective In this paper, we describe the design, development and implementation of the Health Inequality Monitoring channel on the OpenWHO eLearning platform. We discuss the anticipated impact and potential opportunities for these eLearning courses to contribute to strengthened health inequality monitoring practices. Results The Health Inequality Monitoring channel on the OpenWHO platform is a self-directed learning environment, designed to meet the immediate learning needs of users. The channel contains three series of courses: health inequality monitoring foundations courses; topic-specific health inequality monitoring courses; and health inequality monitoring skill building courses. Courses are primarily targeted to monitoring and evaluation officers, data analysts, academics and researchers, public health professionals, medical and public health students, and others with a general interest in health data and inequality monitoring. Conclusions WHO eLearning courses on health inequality monitoring are addressing the need for capacity strengthening in the collection, analysis and reporting of inequality data. They introduce learners to the foundational concepts, best practices, tools and skills required to conduct health inequality monitoring. The courses on the Health Inequality Monitoring channel demonstrate how technical information can be simplified and presented to broad audiences in a manner that is highly accessible to learners. The Health Inequality Monitoring channel on OpenWHO is an innovative and necessary addition to existing tools and resources to support the advancement of health equity.